MANIPULASI FOTOPERIOD UNTUK MEMACU PERKEMBANGAN GONAD IKAN SELAIS (Ompok hypopthalmus) - Mira Rahmita Sari; Windarti Windarti; Sukendi Sukendi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
This researct was conducted on September 2015 to April 2016. Fish reproduction is controlled by endocrine system that is affected by external factors such as photoperiod. Changing in photoperiod may affect the gonad development in fish. To understand the effect of different photoperiod in gonad development of O. hypopthalmus, the fishes were reared in fiber tanks (140 x 60 x 40 cm) with water circulation system and completed with aerator. The treatments applied were : natural photoperiod, 24D (continuous dark), 16D8L (16 hours dark and 8 hours light), 12D12L (12 hours dark and 12 hours light), 8D16L (8 hours dark and 16 hours light) and 24L (25 continuous light), and the fish were feed on shrimp and cricket enriched commercial pellet. The fishes were sampled once/month, 4 fishes/sample. Parameters investigated were body length, body weight, gonad development, hepatosomatic index (HSI), viscerosomatic index (VSI) and gonadosomatic index (GSI). Based on the research results different photoperiod did not affect the gonad development of O. hypopthalmus. There was no special pattern in gonad development in all treatments. The gonads were first developed in 13 – 37 weeks old male and female fishes. The female gonad, however, developed earlier than that of the male. The smallest female with developed gonad was 10.65 cm TL and 5.55 g BW. While that of the male was 16.7 cm TL and 16.7 g BW. During the research there was no mature fish. The HSI and VSI shown similar patterns, it was increased by the second month (17 weeks old fish) and then decreased. This decrement indicates that the energy stored has been used for gonad development. Based on data obtained it can be concluded that the photoperiod does not affect the gonad development of ompok hyopthalmus.